Using Altman Z-Score to Measure the Financial and Banking Stability of the Kurdistan International Islamic Bank for Investment and Development for the Period (2015-2021) - Ghafour Kareem, Safeen; Abdulrahim Aziz, Gulderan (Zanco Journal of Human Sciences, 2023)
The study of the risks of the financial failure of banks is of crucial importance for decision-making by managers to hedge them. Failure problems that reach bankruptcies often occur, especially in banks. Many models formulate to predict financial failure to reduce these worrisome risks, perhaps the Altman model's most prominent. The specificity of Islamic banks makes their investments through a set of investment formulas, which differ from the aspects of Sharia and the different risks of each investment formula from the other. However, many researchers have reached many causes of financial and banking instability, perhaps the most prominent of which is mismanagement, and the efficiency of business operation is a good reflection of the bank's management. This research aims to measure the financial stability of the Kurdistan International Bank in Erbil during the Period 2015-2021. A model was used To measure and analyze the soundness of the performance of the researched bank, as one of the banks within the financial and banking system affected by recent economic changes: The importance of the study stems from the fact that macro prudence indicators and early warning systems can be a permanent and continuous means to guide and warn decision makers and policymakers of the possibility that the banking system, and even the economy as a whole, will be exposed to a financial crisis before it occurs, and take the necessary preventive measures from the occurrence of crises. The research concluded that the average values of the Z score of the bank researched were more significant than the value specified for Z ≥2.6 and all study periods, reflecting the merit and efficiency of management in the Kurdistan International Islamic Bank for Investment and Development.